2011
DOI: 10.1002/jhet.555
|View full text |Cite
|
Sign up to set email alerts
|

Recent development for enantioselective synthesis of aromatic compounds from alkynes via metallacyclopentadienes

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Metallacyclopentadiene, which is recognized as a metallo-heterocycle, is an important intermediate for the formation of aromatic derivatives. In this short review, we summarized the recent advance on construction of axial, central, planar, and helical chirality by transition-metal-catalyzed aromatic compounds formation via metallacyclopentadienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The addition of the alkyne to the iridacyclopentadiene complex proceeded in a concerted manner and should be classified as a metal-assisted Diels−Alder reaction. Interestingly, variable temperature 31 P and 1 H NMR spectra in CDCl 3 showed that all six benzene carbons and the three phosphines were time-average equivalent, indicating that complex 132a was fluxional. EHT calculations demonstrated that the fluxionality was achieved by the movement of the metal over the ring and the rotation of the P 3 Ir + group.…”
Section: Iridium Complexesmentioning
confidence: 58%
See 1 more Smart Citation
“…The addition of the alkyne to the iridacyclopentadiene complex proceeded in a concerted manner and should be classified as a metal-assisted Diels−Alder reaction. Interestingly, variable temperature 31 P and 1 H NMR spectra in CDCl 3 showed that all six benzene carbons and the three phosphines were time-average equivalent, indicating that complex 132a was fluxional. EHT calculations demonstrated that the fluxionality was achieved by the movement of the metal over the ring and the rotation of the P 3 Ir + group.…”
Section: Iridium Complexesmentioning
confidence: 58%
“…Many aspects of this type of process have been studied, including those catalysts that have a high level of activity, types of unsaturated substrates that can participate in the cycloaddition, chemo- and regioselectivity, enantioselectivity, and the applications of these processes especially in the synthesis of natural products. The significance of these [2 + 2 + 2] cycloaddition reactions is clearly seen in the large number of reviews published, particularly in the last 15 years, covering general aspects of the reaction, the involvement of different unsaturations other than alkynes, stereoselective [2 + 2 + 2] cycloadditions, the application of the cycloaddition in the synthesis of relevant organic molecules, and the comparison of mononuclear and dinuclear catalysts in alkyne cyclotrimerization . A further particularly important aspect in this field is the elucidation of the mechanisms that govern the cycloaddition, since it aids in the understanding and improvement of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Metallacyclopentadienes are metal-containing heterocycles, which are considered to be the key intermediates for the formation of aromatic derivatives, particularly in the construction of benzene derivatives from the trimerization of alkynes in the stoichiometric and catalytic reactions [49,50]. The reactions of transition-metal complexes with 1,3-butadiynes provide an important and useful ways approach such type of metal-containing heterocycles.…”
Section: Formation Of Metallacyclopentadienesmentioning
confidence: 99%
“…These virtues were impressively demonstrated in pioneering efforts on catalytic [2+2+2]-cycloadditions, by which a broad range of chiral structures is accessible and thus represents a seminal reaction manifold for stereoselective arene-formation. [1][2][3] Today, the capacity of [2+2+2]-cycloadditions is impressively complemented by various other versatile stereocontrolled methodologies, including benzannulation and cyclisation reactions that were widely applied in numerous substrate-, auxiliary-, reagent-, and catalyst-stereocontrolled processes. The breadth of strategies is also reflected by the variety of stereoinduction modes stemming from interactions with chiral catalysts, reagents or substrates with hitherto existing stereogenic units.…”
Section: Introductionmentioning
confidence: 99%